2019
DOI: 10.2147/ijwh.s208257
|View full text |Cite
|
Sign up to set email alerts
|

<p>Patients with cervical intraepithelial neoplasms show different states of health-related quality of life and different coping styles depending on the choice of therapy: findings from the CIN study</p>

Abstract: PurposeTo examine the effects of type of therapy (conservative therapy vs conization) on the psychosocial well-being of patients with cervical intraepithelial neoplasia grade II (CIN II) in a prospective cross-sectional study designed to simplify future choice of therapy.Patients and methodsIn a cross-sectional study comparing 24 CIN II patients who were treated via conservative therapy with 17 CIN II patients who were treated via conization (not randomized), we examined the association between therapy type an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 24 publications
(25 reference statements)
1
18
0
Order By: Relevance
“…In a recent Australian study in which women were hypothetically diagnosed with CIN2, 80% of younger women preferred active surveillance over surgery, primarily because they were concerned about reproductive harm 23 . Some women in the present study considered undergoing excisional treatment to get rid of the uncertainty and worry, as also suggested elsewhere 14,15 . However, the previous studies suggest that women’s quality of life does not depend on treatment method.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…In a recent Australian study in which women were hypothetically diagnosed with CIN2, 80% of younger women preferred active surveillance over surgery, primarily because they were concerned about reproductive harm 23 . Some women in the present study considered undergoing excisional treatment to get rid of the uncertainty and worry, as also suggested elsewhere 14,15 . However, the previous studies suggest that women’s quality of life does not depend on treatment method.…”
Section: Discussionmentioning
confidence: 60%
“…However, the previous studies suggest that women’s quality of life does not depend on treatment method. One study found that choice of therapy may have an influence on physical quality of life and coping strategies, but not on risk of depression, anxiety or mental well‐being 14 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, this information may reduce the psychological burden associated with active surveillance of CIN2, as reported in previous studies. 37 …”
Section: Discussionmentioning
confidence: 99%